« Immoral persons » : genre et respectabilité dans les traversées transatlantiques depuis Brême et Hambourg au début du XXe siècle - Sarah Marciano (Genre & Histoire)
Drawing on case studies, the following paper highlights the individual consequences of U.S. migration policies in the early 20th century, by focusing on women from the German Empire who crossed the Atlantic. By examining unpublished diplomatic correspondence with American consuls stationed in Germany, this paper aims to explore the grounds upon which expulsion procedures were undertaken; some of these were against allegedly immoral German women, while some targeted men accused of having brought them to the United States for “immoral purposes.” Those suspected of prostitution or any other moral deviance were turned away upon arrival on American soil and even after prolonged residence in the United States in accordance with a series of immigration laws passed by Congress from 1903 onwards. This paper aims to highlight the socio-economic and political considerations behind deportation procedures of women at the turn of the 20th century, to examine their small and large-scale consequences and to underline the gendered dimension of the laws determining access to citizenship.